Giving formulary and drug cost information to providers and impact on medication cost and use: a longitudinal non-randomized study. Issue 1 (December 2016) - Tseng, Chien-Wen; Lin, Grace; Davis, James; Taira, Deborah; Yazdany, Jinoos; He, Qimei; Chen, Randi; Imamura, Allison; Dudley, R.
Abstract Background Providers wish to help patients with prescription costs but often lack drug cost information. We examined whether giving providers formulary and drug cost information was associated with changes in their diabetes patients' drug costs and use. We conducted a longitudinal non-randomized evaluation of the web-based Prescribing Guide (www.PrescribingGuide.com ), a free resource available to Hawaii's providers since 2006, which summarizes the formularies and copayments of six health plans for drugs to treat 16 common health conditions. All adult primary care physicians in Hawaii were offered the Prescribing Guide, and providers who enrolled received a link to the website and regular hardcopy updates. Methods We analyzed prescription claims from a large health plan in Hawaii for 5, 883 members with diabetes from 2007 (baseline) to 2009 (follow-up). Patients were linked to 299 "main prescribing" providers, who on average, accounted for >88 % of patients' prescriptions and drug costs. We compared changes in drug costs and use for "study" patients whose main provider enrolled to receive the Prescribing Guide, versus "control" patients whose main provider did not enroll to receive the Prescribing Guide. Results In multivariate analyses controlling for provider specialty and clustering of patients by providers, both patient groups experienced similar increases in number of prescriptions (+3.2 vs. +2.7 increase, p  = 0.24), and days supply of medications (+141 vs. +129 increase, p  = 0.40) averaged across all drugs. Total and out-of-pocket drug costs also increased for both control and study patients. However, control patients showed higher increases in yearly total drug costs of $208 per patient (+$792 vs. +$584 increase, p  = 0.02) and in 30-day supply costs (+$9.40 vs. +$6.08 increase, p  = 0.03). Both groups experienced similar changes in yearly out-of-pocket costs (+$41 vs + $31 increase, p  = 0.36) and per 30-day supply (−$0.23 vs. −$0.19 decrease, p  = 0.996). Conclusion Giving formulary and drug cost information to providers was associated with lower increases in total drug costs but not with lower out-of-pocket costs or greater medication use. Insurers and health information technology businesses should continue to increase providers' access to formulary and drug cost information at the point of care.